A chronology of climatic downturns through the mid- and late-Holocene: tracing the distant effects of explosive eruptions from palaeoclimatic and historical evidence in northern Europe - Kari Mielikäinen; Jari Holopainen; Marc Macias-Fauria; Mauri Timonen; Samuli Helama (Polar Research, 2013)
Geochronological data of the conifer tree rings in a region sensitive to climatic effects of explosive eruptions were analysed for sudden growth reductions in association with extraordinarily cool reconstructed summer temperatures since 5500 B.C. Tree-ring data came from the stems of living trees and subfossil tree remains collected as increment cores and discs, respectively, from an area of northernmost Finnish Lapland (70–68°N to 30–20°E). Calendar year dates when the tree-ring signatures (i.e., growth reductions and reconstructed temperatures) were concurrent were compared with sulphate data from Greenland ice cores. Previous new evidence are in agreement in demonstrating volcanism behind late-Holocene events in 1601 A.D. and 536 A.D., suggesting that the same causal relationship can be implied further back in time. Our data show that earlier events were found to have occurred in the years 330 B.C., 874 B.C., 1464 B.C., 1584 B.C., 2564 B.C. and 2850 B.C. Interestingly, events of lesser magnitude followed the three major events in 542 A.D., 1453 B.C. and 1579 B.C. by a few years. Natural disasters, and grain crop failures, occurred as a result of these events, as has been documented for the summer of 1601 A.D. through Finnish historical data and broadly in the Northern Hemisphere. Climate has surprised humans during historic and likely pre-historic times, causing sudden alterations in agriculture, ecology and economy, and may do so in the future. We argue that the climate change with the most magnified impacts on society may be a negative temperature anomaly that abruptly decreases resource availability over wide spatial scales.